Evaluating genomic biomarkers associated with resistance or sensitivity to chemotherapy in patients with advanced breast and colorectal cancer. (August 2021) - Guenter, Jolene; Abadi, Shirin; Lim, Howard; Chia, Stephen; Woods, Ryan; Jones, Martin; Rebic, Nevena; Renouf, Daniel J; Laskin, Janessa; Marra, Marco
Introduction: Carcinogenesis is driven by an array of complex genomic patterns; these patterns can render an individual resistant or sensitive to certain chemotherapy agents. The Personalized Oncogenomics (POG) project at BC Cancer has performed integrative genomic analysis of whole tumour genomes and transcriptomes for over 700 patients with advanced cancers, with an aim to predict therapeutic sensitivities. The aim of this study was to utilize the POG genomic data to evaluate a discrete set of biomarkers associated with chemo-sensitivity or-resistance in advanced stage breast and colorectal cancer POG patients. Methods: This was a retrospective multi-centre analysis across all BC CANCER sites. All breast and colorectal cancer patients enrolled in the POG program between July 1, 2012 and November 30, 2016 were eligible for inclusion. Within the breast cancer population, those treated with capecitabine, paclitaxel, and everolimus were analyzed, and for the colorectal cancer patients, those treated with capecitabine, bevacizumab, irinotecan, and oxaliplatin were analyzed. The expression levels of the selected biomarkers of interest ( EPHB4, FIGF, CD133, DICER1, DPYD, TYMP, TYMS, TAP1, TOP1, CKDN1A, ERCC1, GSTP1, BRCA1, PTEN, ABCB1, TLE3, and TXNDC17 ) were reported as mRNA percentiles. Results: For the breast cancer population, there were 32 patients in the capecitabine cohort, 15 in the everolimus cohort, and 12 in the paclitaxel cohort. For the colorectal cancer population, there were 29 patients in the bevacizumab cohort, 12 in the oxaliplatin cohort, 29 in the irinotecan cohort, and 6 in the capecitabine cohort. Of the biomarkers evaluated, the strongest associations were found between Bevacizumab-based therapy and DICER1 (P = 0.0445); and between capecitabine therapy and TYMP (P = 0.0553). Conclusions: Among breast cancer patients, higher TYMP expression was associated with sensitivity to capecitabine. Among colorectal cancer patients, higher DICER1 expression was associated with sensitivity to bevacizumab-based therapy. This study supports further assessment of the potential predictive value of mRNA expression of these genomic biomarkers.